Characterization of Fibrinolytic Proteases from Gloydius blomhoffii siniticus Venom - Suk Ho Choi (Korean Pharmacopuncture Institute, 2011)
Objectives : This study was undertaken to identify fibrinolytic proteases from Gloydius blomhoffii siniticus venom and to characterize a major fibrinolytic protease purified from the venom. Methods: The venom was subjected to chromatography using columns of Q-Sepharose and Sephadex G-75. The molecular weights of fibrinolytic proteases showing fibrinolytic zone in fibrin plate assay were determined in SDS-PAGE (Sodium dodecyl sulfate-polyacrylamide gel electrophoresis) The effects of inhibitors and metal ions on fibrinolytic protease and the proteolysis patterns of fibrinogen, gelatin, and bovine serum albumin were investigated. Results : 1) The fibrinolytic fractions of the three peaks isolated from Gloydius blomhoffii siniticus venom contained two polypeptides of 46 and 59 kDa and three polypeptides of 32, 18, and 15 kDa and a major polypeptide of 54 kDa, respectively. 2) The fibrinolytic activity of the purified protease of 54 kDA was inhibited by metal chelators, such as EDTA, EGTA, and 1,10-phenanthroline, and disulfhydryl-reducing compounds, such as dithiothreitol and cysteine. 3) Calcium chloride promoted the fibrinolytic activity of the protease, but mercuric chloride and cobalt(II) chloride inhibited it. 4) The fibrinolytic protease cleaved preferentially A􀒙-chain and slowly B􀒚-chain of fibrinogen. It also hydrolyzed gelatin but not bovine serum albumin. Conclusions: The Gloydius blomhoffii siniticus venom contained more than three fibrinolytic proteases. The major fibrinolytic protease was a metalloprotease which hydrolyzed both fibrinogen and gelatin, but not bovine serum albumin.